Effect of NAA and thiourea on growth, yield and quality of garlic (Allium sativum L.) (Indian Journal of Arid Horticulture, 2018)
A field experiment was conducted to study the "Effect of NAA and thiourea on growth, yield and quality of Garlic  (Allium sativum L.)” during the rabiseason, 2017-18 at the Horticulture Farm, S.K.N. College of Agriculture, Jobner (Rajasthan).  The experiment consisted of twenty treatment combinations including five NAAand Thiourea levels (control, NAA@ 100 ppm,  NAA@ 200 ppm, Thiourea @ 100 ppm and Thiourea @ 200 ppm). They were under taken in factorial randomized block design  with three replications. The results of the study clearly indicated that foliar application of thiourea @ 200 ppm to the garlic crop  significantly increased the plant height (cm), number of leaves per plant, chlorophyll content in leaves, fresh weight of leaves,  neck thickness, polar diameter, fresh weight of bulb, number of cloves per bulb, bulb yield (134.58 q/ha) and quality attributes viz.,  TSS, sulphur, protein content, nitrogen content and ascorbic acid) and net returns (Rs. 1,08,062 /ha) and B: C ratio (1.34) as  compared to control.
Keywords: NAA; thiourea; growth; yield; garlic